New distribution record of the rock shrimp, Sicyonia parajaponica Crosnier, 2003 from Indian waters - Rajool Shanis, C. P.; Akhilesh, K. V.; Ganga, U.; Pillai, N. G. K. (Indian Journal of Fisheries, 2013)
The present study reports the first record of rock shrimp, Sicyonia parajaponica Crosnier, 2003 from Indian waters. The diagnosis of the new record was based on the examination of two male and one female specimens, collected from a commercial trawler operating in the Arabian Sea off the south-west coast of India during December 2010. Present report of S. parajaponica from the Arabian Sea fills the gap in its known distribution range from South China Sea to Gulf of Aden at 10 to 200 m depths.